Analisis Pengaruh Motivasi terhadap Loyalitas Pemain Game Mobile Legends - Mohammad Arsyad Islamay Fasha; Fahreza Ihsan Putra; Adrian Azhar Wijanarko (VISA: Journal of Vision and Ideas, 2024)
Growing technology is influencing the emergence of the internet and new innovations. One of them is the emergence of virtual games that connect between players even with unlimited distances. A virtual game that is currently being favored by all people, namely Mobile Legends. This application provides interesting facilities for many users of the game. The connection between players and the facilities provided can be one of the driving factors that motivate users to continue playing the game. This study was conducted to determine the level of influence of motivation on user loyalty mobile game Legend. Sampling technique is done through the Google Form platform and the dissemination of questionnaires with purposive sampling techniques and inferential statistical methods. The results of this study shows that the influence both of intrinsic and extrinsic motivation has a very strong effect of 69.8% on user loyalty.